(untitled) (Nigerian Journal of Physiological Sciences, 2020)
This study highlighted the effect of Carbendazim on the testicular micro and intermediate filaments adult male African catfish (Clarias gariepinus). Previous studies related to carbendazim toxicity in fish have been limited to mortality patterns and degree of sensitivity across species. Literature on actual pathology in fish is scanty. The fish were exposed to a pre-determined sub-lethal concentration (1.4 mg/L) of Carbendazim for seven and fourteen days, 10 fish were sedated by cold shock, and sacrificed on days seven and 14. Another untreated group (control) were sacrificed at the same periods. The testes were harvested and weighed. Testicular actin microfilament, cytokeratin, desmin and vimentin intermediate filaments were determined using standard immunohistochemistry protocols. Variations in the intensity and pattern of immuno-expression of the testicular actin, cytokeratin, desmin and vimentin were significant in a phase dependent manner with day 14 being more pronounced. Immunohistochemical features of degenerated and necrotic germinal and Sertoli cells in the treated group, with loss of wire-mesh network which supported the mature germinal cells in the testicular lumen were also observed. A sub-lethal dose of carbendazim exposure for either seven or 14 days, induced deliterous changes in the testicular micro- and intermediate filaments, of the African catfish. This portends a reduction in the male reproductive potentials of the exposed species and resultant negative impact on production